2019
DOI: 10.1109/access.2019.2923689
|View full text |Cite
|
Sign up to set email alerts
|

Random Noise Suppression of Magnetic Resonance Sounding Oscillating Signal by Combining Empirical Mode Decomposition and Time-Frequency Peak Filtering

Abstract: Magnetic resonance sounding (MRS) signals are always corrupted by random noise. Although time-frequency peak filtering (TFPF) has been proven to be an effective method to suppress the random noise, it shows shortcomings when processing the oscillating high-frequency MRS signal at about 2 kHz. In this study, a new method combining empirical mode decomposition (EMD) and TFPF is proposed to overcome the TFPF limitation when processing the MRS oscillating signal. With the help of EMD decomposition characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…(1) MMF [23] is first extended with multi-scale parameters to construct MFPs. Experimental comparison has demonstrated that this extension is helpful and effective for improving classification performance [20]. In the present study, the proposed MFPs not only improve the homogeneity of a target but also the separability of the ground target under consideration.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…(1) MMF [23] is first extended with multi-scale parameters to construct MFPs. Experimental comparison has demonstrated that this extension is helpful and effective for improving classification performance [20]. In the present study, the proposed MFPs not only improve the homogeneity of a target but also the separability of the ground target under consideration.…”
Section: Introductionmentioning
confidence: 69%
“…(1) The proposed MFPF provided competitive accuracies in land cover classification of VHR remote sensing images. As an extension of MMF [20], the proposed MFPF achieved the best accuracy compared with that of the MMF, MF, MedF, and the raw image without any filter processing Furthermore, the results of the second experiment indicated that the proposed MFPF is more robust for the different classifiers compared with that of the MF, MedF, and MMF. In addition, the classification results achieved by the proposed MFPF clearly demonstrated its effectiveness and superiority in terms of visual performance and quantitative accuracies compared with those based on the classical spatial-spectral feature extraction approaches, including EPFs [26], RFs [27], M_EMPs [25], and RGF [28].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Time-frequency peak filtering (TFPF) proposed by Bouake and Mostefa [4], is an effective method for suppressing Gaussian noise in non-stationary deterministic limited-band signals, which has the advantages of wide applicability and requiring less additional information. Therefore, this method has been successfully applied in the fields of seismic monitoring [5], Electro Encephalo Graphy (EEG) signal enhancement [6], frequency hopping signal detection [7] and mechanical fault diagnosis [8], showing a good suppression effect on strong random noise. It should be noted that the window length of TFPF plays an important role in balancing noise suppression ability and signal fidelity.…”
Section: Introductionmentioning
confidence: 99%
“…The model-based method [16], the wavelet-based method [17] and the non-linear energy operator [14] have been proposed in dealing with the spike noise. For random noise attenuation, the stacking method [13], the time-frequency peak filtering method [7,18] and intensive sampling sparse reconstruction and kernel regression estimation [19] are investigated. Although all these methods have obtained good results in MRS noise suppression, they still have some disadvantages.…”
Section: Introductionmentioning
confidence: 99%